ABRASION HAZARD ANALYSIS IN BANGGAI LAUT REGENCY CENTER OF SULAWESI - Putra, Ahmad Pratama (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
This study on potential abrasion hazards in Banggai Laut Regency is intended to determine the abrasion points on the entire coast and provide alternative abrasion hazard mitigation solutions. The process of identifying abrasion disasters in the Banggai Laut Regency uses a manual interpretation method by considering several variables including coastal morphology, bathymetry, abrasion event history, the degree of coastal slope, coastal geology, and the position of the coast towards the coming wind direction. These six factors are given equal weight to their contribution to the identification of the potential for abrasion. The results of the interpretation of the identification of the potential for abrasion are indicative abrasion potential boundaries with high potential values (red), medium (yellow), and low (green). All coastlines in Banggai Laut Regency have high, medium or low abrasion potential. Most of the abrasions that have occurred in Banggai Laut Regency are in the morphology of the bay. Coastal morphology and the position of the coast towards the direction of wind coming from the high seas are the main variables causing the occurrence of high abrasion hazards in the Banggai Laut Regency. Alternative methods of handling abrasion can be in the form of mitigation of structural and non-structural abrasion hazards.